A remote sensing assessment of irrigation land use land cover change in the Sokoto Rima River Basin, Nigeria - Abdulmajid, Aminu (Department of Environmental and Geographical Science, 2022)
This study examines the expansion and utilisation of Fadama irrigation in the Sokoto Rima River Basin using the ground yield and remote sensing data. Decadal land use land cover (LU/LC) change detection was conducted using remotely sensed data from Landsat 4,5,7 ETM for 1988, 1998 and Landsat 8 OLI for 2018 using a digital classification and a cloud-based classification provided by Google Earth Engine (GEE) API, with an overall accuracy of 97% in 1988, 92% in 1998 and 90% in 2018. Additionally, the Normalised Difference Vegetation Index (NDVI) derived from MODIS, GEE NDVI, and the Landsat was used to assess the crop yield patterns of the irrigation farming at the Fadama sites in conjunction with the limited ground yield data from 2000-2005, and was found to be a positive change over the years. The result generated from the classification was juxtaposed with observable field characteristics of the LU/LC identified. The decadal trend between 1988 to 1998 saw an increase of 114% in dam surface water and 166% of the natural vegetation, while the nonvegetated areas and the Fadama areas decreased in size by -100% and -65% respectively. Between 1998 and 2018, the reverse of the previous pattern was observed, with water and vegetated areas decreasing in their surface area in hectares by -80% and -23% respectively. Non-vegetated areas increased by 3% while Fadama areas increased in size by 112%, indicating that the Fadama areas were under-utilised by - 65% of the total hectarage in the past, and in recent years a 47% increase was recorded between the two periods. In addition, the Standardised Precipitation and Evapotranspiration Index (SPEI) data from 1950 was used to analyze the meteorological and hydrological drought pattern at four locations within the basin and was found to be a moderate drought. The SPEI data was then correlated with the Global Surface Water Explorer data to observe the surface water dynamics and to show the drought extent around Bakolori, Goronyo, Jibia, Wurno and Zobe dams. The result showed that the dams are shrinking in size due to risen temperature and consequent evaporation caused by moderate drought and water use for irrigation. Lastly, this research uncovers the utilization of the Fadama in recent years by 47%, but with mismanagement of the resources in the Sokoto Rima River floodplain because not all the irrigation fields are put into cultivation, with 39,907 ha put into use from the planned irrigation of 105,472 ha in the entire basin. Therefore, this research recommends a proper intervention of the government to promote and enhance sustainable management of the Fadama lands, water, and the vegetation resource. This should be done in consideration of the deteriorating climate to close yield gaps, with much emphasis on engaging the local farmers by monitoring yearly ground yield data and ensuring all incentives are distributed effectively to brace an active and sustainable management of the entire basin and its vast resource.